Determination of Polyphenol Components of Korean Prostrate Spurge (Euphorbia supina) by Using Liquid Chromatography—Tandem Mass Spectrometry: Overall Contribution to Antioxidant Activity - Yi Song; Sung Woo Jeong; Won Sup Lee; Semin Park; Yun-Hi Kim; Gon-Sup Kim; Soo Jung Lee; Jong Sung Jin; Chi-Yeon Kim; Ji Eun Lee; Se Yun Ok; Ki-Min Bark; et al. (Journal of Analytical Methods in Chemistry)
The Korean prostrate spurge Euphorbia supina is a weed that has been used in folk medicine in Korea against a variety of diseases. Nine polyphenols were characterized for this plant by using high-performance liquid chromatography-tandem mass spectrometry (HPLC-MS/MS) and the results were compared with the literature data. The individual components were validated using the calibration curves of structurally related external standards and quantified for the first time by using the validated method. Correlation coefficients (r2) were >0.9907. The limit of detection and limit of quantification of the method were >0.028 mg/L and 0.094 mg/L, respectively. Recoveries measured at 50 mg/L and 100 mg/L were 76.1–102.8% and 85.2–98.6%, respectively. The total amount of the identified polyphenols was 3352.9 ± 2.8 mg/kg fresh plant. Quercetin and kaempferol derivatives formed 84.8% of the total polyphenols. The antioxidant activities of the flavonoids were evaluated in terms of 1,1-diphenyl-2-picrylhydrazyl and 2,2′-azinobis(3-ethylbenzothiazoline-6-sulfonic acid) radical cation-scavenging activity, and the reducing power showed a dose-dependent increase. Cell viability was effectively suppressed at polyphenol mixture concentrations >250 mg/L.